The accuracy of four formulas for LDL-C calculation at the fasting and postprandial states - Xu, Jin; Du, Xiao; Zhang, Shilan; Xiang, Qunyan; Zhu, Liyuan; Liu, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background Elevated level of low-density lipoprotein cholesterol (LDL-C) is concerned as one of the main risk factors for cardiovascular disease, in both the fasting and postprandial states. This study aimed to compare the measured LDL-C with LDL-C calculated by the Friedewald, Martin–Hopkins, Vujovic, and Sampson formulas, and establish which formula could provide the most reliable LDL-C results for Chinese subjects, especially at the postprandial state. Methods Twenty-six subjects were enrolled in this study. The blood samples were collected from all the subjects before and after taking a daily breakfast. The calculated LDL-C results were compared with LDL-C measured by the vertical auto profile method, at both the fasting and postprandial states. The percentage difference between calculated and measured LDL-C (total error) and the number of results exceeding the total error goal of 12% were established. Results The calculated LDL-CF levels showed no significant difference from LDL-CVAP levels at the fasting state. The calculated LDL-CS were significantly higher than LDL-CVAP at the fasting state (P < 0.05), while the calculated LDL-Cs were very close to LDL-CVAP levels after a daily meal. At the fasting state, the median total error of calculated LDL-CF was 0 (quartile: −3.8 to 6.0), followed by LDL-CS, LDL-CMH, and LDL-CV. At the postprandial states, the median total errors of LDL-CS were the smallest, 1.0 (−7.5, 8.5) and −0.3 (−10.1, 10.9) at 2 and 4 h, respectively. The calculated LDL-CF levels showed the highest correlation to LDL-CVAP and accuracy in evaluating fasting LDL-C levels, while the Sampson formula showed the highest accuracy at the postprandial state. Conclusion The Friedewald formula was recommended to calculate fasting LDL-C, while the Sampson formula seemed to be a better choice to calculate postprandial LDL-C levels in Chinese subjects.